ENGLISH LECTURERS` PREFERENCES IN CORRECTING STUDENTS` RESEARCH REPORT WRITING ERRORS (A Study at IAIN Raden Intan English Department) - Kurniawan, Iwan (Universitas Islam Negeri Raden Intan Lampung, 2015)
Although there are pros and contras about the benefits of writing errors correction, error correction is believed very useful in writing process. Due to its benefit, this research tried to describe the preferences of IAIN Raden Intan English lecturers in correcting students` research report or Skripsi. The investigation explored issues regarding techniques used by lecturers in correcting writing errors, error symbols used, and kind of corrected errors. To know the answers, questionnaires were deployed to those lecturers. Findings show that favourite technique was consulting grammar book & dictionary, underline was the most often used symbol and grammar was the most corrected error.